2010
DOI: 10.1007/dcr.0b013e3181d5e2ee
|View full text |Cite
|
Sign up to set email alerts
|

Single-Access Laparoscopic Left and Right Hemicolectomy Combined With Extracorporeal Magnetic Retraction

Abstract: This procedure can be safely and feasibly performed using extracorporeal magnetic retraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 15 publications
2
23
0
Order By: Relevance
“…This method is extremely effective; however, insertion of the anvil into the colon is rather complex. Uematsu et al [41] reported another SILS technique that uses movement of an extracorporeal magnet to retract the tissue grasped by a magnetized intracorporeal short vascular clip. This interesting method allows mesenteric dissection to be facilitated by effective countertraction; however, it requires the use of a special sterilized magnet.…”
Section: Discussionmentioning
confidence: 99%
“…This method is extremely effective; however, insertion of the anvil into the colon is rather complex. Uematsu et al [41] reported another SILS technique that uses movement of an extracorporeal magnet to retract the tissue grasped by a magnetized intracorporeal short vascular clip. This interesting method allows mesenteric dissection to be facilitated by effective countertraction; however, it requires the use of a special sterilized magnet.…”
Section: Discussionmentioning
confidence: 99%
“…Single-incision laparoscopic techniques have been utilized in most colorectal procedures for which standard laparoscopic techniques are used, including right and left colectomy, sigmoid colectomy, low anterior resection, and total proctocolectomy [11][12][13][14][15][16][17][18]. The most frequently reported single-incision operation in colorectal surgery has been right hemicolectomy.…”
mentioning
confidence: 99%
“…The Hospital de Clínicas in Buenos Aires has reported the clinical use of magnetized instruments (NdFeB) for single site laparoscopy [15], [16]. Clinical investigation of single-port laparoscopic colectomy was demonstrated to be safe and effective with the aid of magnetic retraction by Uematsa et al [17] while single site laparoscopy investigations by Cho et al have been limited to canine ileocecectomy (resection of the lower small intestine) [18]. In one of the only clinical examples of an electromagnet used for coupling, Kobayashi et al [19] demonstrated the use of the Pentax-developed magnetic anchoring system.…”
Section: A Clinical Backgroundmentioning
confidence: 99%